Training load in relation to loading and unloading phases of training (AIS, 2021)
This can be used by coaches, performance support team members and organisations in the national high performance sport system as a resource to guide conversations relating to holistic approaches to well-periodised and individualised training load planning following unloading. In 2015, the first version of this was published as part of a multi-disciplinary project including the AIS Disciplines of Medicine, Strength and Conditioning, Sports Nutrition, Physiology, and Physical Therapies. Version 2 has been developed in consultation with representatives from the National Institute Network and National Sporting Organisations with input from experts in the wider professional sport and university sectors.